Post-modernism in Iraqi Planning Experience - Nouri Hassan, A (KnE Engineering, 2018)
Iraq faces several problems as a result of its engagement in several wars, which brought great consequences. Wars continued for nearly a century. Iraq was in a position of continuously watching and defending for its national identity and existence. This was reflected negatively on its economy, society, and its environment and progress. According to these facts, it is difficult for this country to have the opportunity to be involved in an intellectual and philosophical dialogs such as (post modernism issue) for the sake of imitating developed, safe, and economically settled countries. This paper presents the existing situation of Iraq and type of problems facing it, and the consequences facing its reality. Also, giving solutions for its problems and proposing to postpone the intellectual dialogs for another stage.